Genetic Causes of Familial Adenomatous Polyposis (FAP), Risk Factors and Clinical Outcomes - Mohammad Mehdi Heidari; Elham Afkhami aqhda; Maryam Tahmasebi; Mehri Khatami; Zahra Shaker Ardakani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2024)
Introduction: Familial adenomatous polyposis (FAP) is a hereditary disorder that is the most common colon cancer syndrome in an autosomal dominant form. At first, germline mutations in the APC gene (adenomatous polyposis) were identified as the main genetic factor causing FAP, but during subsequent studies, the human MutY (MYH) gene with an autosomal recessive pattern was also identified as the factor causing this disease, which is commonly referred to as MutYH-dependent apoptosis (MAP). FAP and MAP present with an early onset of hundreds of adenomatous polyps in the colon, at a median age of 35–40 years, and are associated with a significantly increased risk of colon cancer (CRC). In some other patients, gastrointestinal polyps, congenital hypertrophy in the retinal pigment epithelium, desmid tumors, and extracolonic malignancies are seen. The common treatment method in patients is through endoscopic and surgical methods. However, the patients with FAP and their relatives should receive appropriate genetic counseling. The purpose of this review article was to describe and investigate the clinical aspects and genetic diseases of FAP and MAP. For this purpose, the latest articles related to FAP genetic disease were selected by searching Google Scholar and PubMed sources. Conclusion: Despite the progress made in discovering the molecular mechanisms of FAP, its genetic factors are still not fully understood. A deeper understanding of the molecular biology and genetics of this disease can lead to healthy therapies that can be used to rezone intestinal polyps and neoplastic malignancies and be a new target for future treatment.